Antibiotic resistance and biofilm-forming properties of bacteria from horses’ wound - Ahmad Nadzir, Nur Adilah (2017)
Wounds occur commonly in horses, whether surgical or accidental. The moisture and warmness of the wound provides essential environment for the growth of microorganism. It has been suggested that chronic, non healing wounds may results from biofilm where there is increased antimicrobial resistance of the bacteria residing in biofilms. Therefore presence of resistant organism in chronic wounds further complicates the problem. This research was conducted to identify bacteria on wounds, ability to form biofilm and antibiotic susceptibility of planktonic and biofilm state of bacteria. A total of 122 bacterial isolates were obtained from 30 horses’ woundbetween January 2015 to June 2015. Eighty-one were Gram-negative (66.4%) and 41 were Gram-positive (33.6%). The predominant organisms isolates were Escherichia coli (26.2%), Enterobacter sp (20.0%), Staphylococcus sp(16.9%), Streptococcus sp (6.2%) and Acinetobacter sp (4.6%). The isolates were then tested for antibiotic susceptibility test, biofilm forming potential (BFP), minimum inhibitory concentration (MIC) and minimum biofilm eradication concentration (MBEC). Gentamycin and Levofloxacin were found to be effective in inhibiting both Gram-negative and Gram-positive bacteria. Thirteen (27.1%) of 48 isolates that constitute of the predominant isolates were found to be multidrug resistant (MDR) with MDR E. coli (4.2%), MDR Enterobacter (10.4%), MDR Staphylococcus (10.4%), MDR Streptococcus (2.1%). 96-well microtiter plates biofilm production revealed that 83.3% (40/48) were biofilm forming. While the antibiotic sensitivities of biofilm organisms tested by MBEC assays were lower than the antibiotic sensitivities of the same organisms in their planktonic state, as tested by MIC assays. These data suggest the prevalence of biofilm in wounds may contribute to prolonged healing and antibiotic tolerance thus plays a role in wound management in horses.